When teaching gets tough – Professional community inhibitors of teacher-targeted bullying and turnover intentions. (November 2015) - Pyhältö, Kirsi; Pietarinen, Janne; Soini, Tiina
Bullying in school has become an international concern in recent decades. Yet, we know surprisingly little about inhibitors of teacher-targeted bullying. The study focused on exploring the interrelation between the teacher–working environment fit, bullying, experienced exhaustion and turnover intentions. Altogether 2310 comprehensive school teachers completed the professional agency survey. The analysis was carried out using structural equation modelling (SEM). The results confirmed that the teacher–working environment fit, that is, receiving collegial support and acknowledgement, combined with a positive professional climate and ability to solve problems constructively, can function as inhibitors of both teacher-targeted bullying and exhaustion. Also, a modest reciprocal relationship between bullying and experienced exhaustion was detected. The study further showed exhaustion and bullying to be significant determinants of teacher turnover.